Determination of the microscopic acid dissociation constant of piperacillin and identification of dissociated molecular forms - Li, Guoao; Wang, Yaling; Sun, Chengyi; Liu, Fei (Frontiers in Chemistry, 2023)
For amphoteric ß-lactam antibiotics, the acid dissociation constant (pKa) is a fundamental parameter to characterize physicochemical and biochemical properties of antibiotics and to predict persistence and removal of drugs. pKa of piperacillin (PIP) is determined by potentiometric titration with a glass electrode. Electrospray ionization mass spectrometry (ESI-MS) is creatively applied to verify the reasonable pKa value at every dissociation step. Two microscopic pKa values (3.37 ± 0.06 and 8.96 ± 0.10) are identified and attributed to the direct dissociation of the carboxylic acid functional group and one secondary amide group, respectively. Different from other ß-lactam antibiotics, PIP presents a dissociation pattern where direct dissociation is involved instead of protonation dissociation. Moreover, the degradation tendency of PIP in an alkaline solution may alter the dissociation pattern or dismiss the corresponding pKa of the amphoteric ß-lactam antibiotics. This work offers a reliable determination of the acid dissociation constant of PIP and a clear interpretation of the effect of stability of antibiotics on the dissociation process.